1997
DOI: 10.1159/000127168
|View full text |Cite
|
Sign up to set email alerts
|

Hexarelin Stimulation of Growth Hormone Release and mRNA Levels in an Infant and Adult Rat Model of Impaired GHRH Function

Abstract: Hexarelin, a GH-releasing peptide, is an effective GH secretagogue in man and a variety of experimental animals. In the present study, we sought to characterize the effects of short-term Hexarelin treatment on GH release and GH mRNA levels in infant and young-adult rats and in rats of either age passively immunized with an antiserum against GHRH (GHRH-Ab). Hexarelin (80 µg/ kg, b.i.d. s.c), administered for 3, 5 or 10 days to 8-, 6- and 1-day-old rats, respectively, induced a progressive enhancement of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…A similar pattern had been demonstrated in the early phases of hexarelin administration in old dogs, in which, however, even during the off-periods of the peptide treatment, baseline GH concentrations remained higher than pretreatment values (18). In infant GHRH-deprived rats, treatment with hexarelin for 3 or 5 days increased pituitary GH mRNA (35), whereas, given for 5-10 days to young 'intact' adult rats, it was ineffective in this context (36). Also worth noting in this context is that, in young GHRH-deprived rats, a 10-day treatment with hexarelin increased the expression of its own receptors in the pituitary (R Nass & A Torsello, unpublished results).…”
Section: Discussionsupporting
confidence: 73%
“…A similar pattern had been demonstrated in the early phases of hexarelin administration in old dogs, in which, however, even during the off-periods of the peptide treatment, baseline GH concentrations remained higher than pretreatment values (18). In infant GHRH-deprived rats, treatment with hexarelin for 3 or 5 days increased pituitary GH mRNA (35), whereas, given for 5-10 days to young 'intact' adult rats, it was ineffective in this context (36). Also worth noting in this context is that, in young GHRH-deprived rats, a 10-day treatment with hexarelin increased the expression of its own receptors in the pituitary (R Nass & A Torsello, unpublished results).…”
Section: Discussionsupporting
confidence: 73%
“…However, previous studies indicated that the GH-secreting activity of hexarelin was largely impaired in the GHD rat model (8). Like other GHSs, hexarelin requires the presence of endogenous GHRH for maximal stimulation of GH secretion (8,9), because passive immunization against GHRH blunts hexarelin-induced GH secretion (10).…”
mentioning
confidence: 99%
“…The antiserum against GHRH (GHRH-Ab; a generous gift of Dr. William B. Wehrenberg) had been fully tested and found to be effective in blunting body growth [25, 26, 27, 31]. Based on those studies, the dose of 100 µl/rat for 10-day-old rats and 500 µl/rat for young adult rats were chosen since they reproducibly resulted in maximal inhibition of GH secretion.…”
Section: Methodsmentioning
confidence: 99%
“…The length of treatment with hexarelin and GHRH was chosen based on previous experiments [31]in which we demonstrated that 5 and 10 days of hexarelin treatment were needed to stimulate an increase in GH mRNA in GHRH-deficient neonatal and young adult rats, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation